Sequential supplementary firing in natural gas combined cycle with carbon capture: A technology option for Mexico for low-carbon electricity generation and CO2 enhanced oil recovery. (August 2016) - González Díaz, Abigail; Sánchez Fernández, Eva; Gibbins, Jon; Lucquiaud, Mathieu
Highlights: Sequential supplementary firing increases CO2 concentration for additional production for EOR. The additional fuel increases heat available for steam generation in the combined cycle. It results in lower capital costs due to the reduction by half of the number of gas turbine, volume of flue gas and absorber train. It is advantageous for EOR at gas prices up to 6/MMBTU, e.g. in North America at current gas and CO2 prices. Abstract: Combined cycle gas turbine power plants with sequential supplementary firing in the heat recovery steam generator could be an attractive alternative for markets with access to competitive natural gas prices, with an emphasis on capital cost reduction, and where supply of carbon dioxide for Enhanced Oil Recovery (EOR) is important. Sequential combustion makes use of the excess oxygen in gas turbine exhaust gas to generate additional CO2, but, unlike in conventional supplementary firing, allows keeping gas temperatures in the heat recovery steam generator below 820 °C, avoiding a step change in capital costs. It marginally decreases relative energy requirements for solvent regeneration and amine degradation. Power plant models integrated with capture and compression process models of Sequential Supplementary Firing Combined Cycle (SSFCC) gas-fired units show that the efficiency penalty is 8.2% points LHV compared to a conventional natural gas combined cycle power plant with the same capture technology. The marginal thermal efficiency of natural gas firing in the heat recovery steam generator can increase with supercritical steam generation to reduce the efficiency penalty to 5.7% points LHV. Although the efficiency is lower than the conventional configuration, the increment in the power output of the combined steam cycle leads a reduction of the number of gas turbines, at a similar power output to that of a conventional natural gas combined cycle. This has a positive impact on the number of absorbers and the capital costs of the post combustion capture plant by reducing the total volume of flue gas by half on a normalised basis. The relative reduction of overall capital costs is, respectively, 15.3% and 9.1% for the subcritical and the supercritical combined cycle configurations with capture compared to a conventional configuration. For a gas price of 2/MMBTU, the Total Revenue Requirement (TRR) – a metric combining levelised cost of electricity and revenue from EOR – of subcritical and supercritical sequential supplementary firing is consistently lower than that of a conventional NGCC by, respectively, 2.2 and 5.7 /MWh at 0 /t CO2 and by 4.9 and 6.7 /MWh at 50/t CO2 . At a gas price of 4/MMBTU and 6/MMBTU, the TRR of a subcritical configuration is consistently lower for any carbon selling price higher than 2.5 /t CO2 and 37 /t CO2 respectively.